"It seems kinda like a different language to us": Homeless youths' attitudes and experiences pertaining to condoms and contraceptives. (16th March 2019) - Begun, Stephanie; Combs, Katie Massey; Torrie, Michaela; Bender, Kimberly
ABSTRACT: Homeless youth become pregnant or involved in pregnancies at high rates. There are many ways by which unintended pregnancies may be prevented, including the use of condoms and other contraceptives. However, there is a dearth of research regarding contraceptive use among this vulnerable youth population, and especially through lenses that consider homeless youths' diverse gender identities, expressions, and sexualities. This study qualitatively explores homeless youths' attitudes and experiences regarding condom and other contraceptive use. Data were obtained from interviews with 30 youth experiencing homelessness, ages 18–21. Youth reported inconsistent use of condoms and other contraceptives, which youth often attributed to their perceptions of contraceptive inaccessibility and exorbitant cost. Most youth also did not know where to obtain contraceptive information and services, and reported transportation barriers and fear of being stigmatized in health care settings, particularly in relation to their gender identities and sexualities. Findings suggest that reproductive and sexual health information and services are urgently needed by all homeless young people, and from low-barrier, non-judgmental, and empathetic sources.